2016
DOI: 10.2474/trol.11.174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tribochemical Reaction on Friction and Wear Behavior of Metallic Materials in <i>n</i>-Hexane and in Ethanol

Abstract: Cast iron, aluminum metal and sintered aluminum-silicon (Al-Si) were slid against SUS440C stainless steel in n-hexane and in ethanol. In the case of the cast iron/stainless steel and aluminum metal/stainless steel pairs, friction and wear were lower in n-hexane than in ethanol. In contrast, the friction and wear for the sintered Al-Si/stainless steel pair were much higher in n-hexane than in ethanol. The results from morphological observations and chemical analyses of the worn surfaces suggested that the wear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Iron based materials such as steel and cast iron are widely used for piston rings and cylinder linings [6]. We have previously reported that adhesive wear occurs on the surfaces of SUS440C stainless steel disks and an FC250 cast iron disks slid against a SUS440C stainless steel pin in ethanol [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Iron based materials such as steel and cast iron are widely used for piston rings and cylinder linings [6]. We have previously reported that adhesive wear occurs on the surfaces of SUS440C stainless steel disks and an FC250 cast iron disks slid against a SUS440C stainless steel pin in ethanol [7,8].…”
Section: Introductionmentioning
confidence: 99%